Impact of Green Transformational Leadership on Environmental Performance Through Green HRM Practices and Creativity in the Hotel Industry of Pakistan (KASBIT Business Journal, 2023)
AbstractBased on resource-based view (RBV) and ability-motivation opportunity (AMO) theoretical lenses, this study investigated the missing links of green HRM and green creativity through which green transformational leadership (GTFL) enhances environmental performance. Moreover, environmental beliefs and values (EV&B) was evaluated as moderating factor in the model. Through survey questionnaire, data was collected from 170 hotels in two major cities of Pakistan: Lahore and Islamabad. Data was analyzed through partial least square-based structural equation modelling (PLS-SEM) technique using Smart PLS 0.3.  The study found that green HRM and green creativity significantly mediates the relationship between GTFL and environmental performance. However, the moderating role of EV&B was found insignificant in the results. The findings imply that the pro-environmental leadership is the critical resource that enables environmental performance through enhancing critical employees’ competency (i.e. green creativity) and institutionalizing required processes (i.e. green HRM) in the organization.     Keywords: Green HRM; green transformational leadership; creativity; environmental performance, RBV
Keywords: Green HRM; green transformational leadership; creativity; environmental performance; resource-based view